Combined surgery and endoluminal vacuum therapy for bronchial fistula and esophageal leakage after surgery for synchronous lung and esophageal cancer - Gabryel, Piotr; Sielewicz, Magdalena; Smoliński, Szymon; Dobiecki, Tomasz; Piwkowski, Cezary (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2022)
Simultaneous esophageal resection and pulmonary lobectomy for synchronous esophageal cancer and lung cancer is associated with an increased risk of postoperative complications, including esophageal leakage and broncho-pleural fistula [1]. Endoluminal vacuum therapy (EVT) has been reported to be effective in the treatment of anastomotic leak after esophageal resection [2]. However, in the event of a bronchial fistula, EVT may cause significant air leakage through the fistulas, which may eventually lead to respiratory complications and impede negative pressure treatment. Here we present a patient with bronchopleural and esophagopleural fistula successfully treated with surgery and EVT.